Obezite Cerrahisi (Bariatrik Cerrahisi) Öncesi ve Sonrası Dönemde Hastaların Depresyon, Beden Memnuniyeti ve Yeme Tutumunun Değerlendirilmesi - Tuna, Neşe (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Obesity requires a multidisciplinary treatment. Obesity can be treated in two ways; including medical and surgical treatments. Surgical treatment, known as Bariatric surgery and comprising a series of operations are performed. Three kinds of scale were used to the 60 patients before and after bariatric operatation. These scales are; 1) Beck Depression Inventory, 2) Eating Attitudes Test3) Multidimensional Body-Self / Essence is the relationship scale. The mean and standard deviation of BKĠ variable for preoperative and postoperative were found significatly differemce as follows; 44.42 ± 5.27, 31.03 ± 3.848 respectively (p <0.001). Mean and standard deviation values of the Beck Depression Inventory preoperative and postoperative were found significatly differemce as follows; 28.15 ± 8.745, 9.450 ± 5.779 respectively (p <0.001). These results were found for Multidimensional Body Self / Self Relationship Questionnaire 225.3 ± 28.79, 149.8 ± 28.15 (p<0.001) and for Eating Attitudes Test results; found as 47.96 ± 15.71, 29.26 ± 8.38 This diferences was determined to be significantly different (p <0.001). Studies showed that effective weight loss was found in bariatric surgery. It has been found that the quality life is increased. Finally, it was found that the patients felt themselves better and healtier in psychological, physical and metabolic situation.

ÖZ: Obezite, multidisipliner bir tedavi gerektirmektedir. Obezite medikal ve cerrahi olmak üzere iki yöntemle tedavi edilmektedir. Cerrahi tedavisinde Bariatrik cerrahi olarak bilinen ve bir dizi ameliyatları içeren tedavi yöntemi uygulanmaktadır ÇalıĢmaya obez olan 60 hasta dâhil edilmiĢ, ameliyat öncesi ve sonrası üç farklı ölçek kullanılarak veriler elde edilmiĢtir. Bunlar sırasıyla; 1) Beck Depresyon Envanteri, 2) Yeme Tutumu Testi3) Çok Yönlü Beden-Benlik/Öz ĠliĢki ölçeğidir. Hastaların ameliyat öncesi BKĠ değiĢkeninin ortalama ve standart sapma değeri; 44,42 ± 5,27 iken ameliyat sonrasında 31,03 ± 3,848‟e kadar düĢtüğü ve bu düĢüĢün istatistiksel olarak önemli düzeyde olduğu bulunmuĢtur (p<0.001). Hastaların ameliyat öncesi BECK Depresyon Envanteri ortalama ve standart sapma değeri; 28,15 ± 8,745 iken ameliyat sonarsı bu değer; 9,450 ± 5,779 kadar düĢmüĢtür. Çok Yönlü Beden Benlik/Öz ĠliĢki Ölçeği için ilgili değerler; 149,8 ± 28,15, 225,3 ± 28,79 kadar yükseldiği, yeme tutum testi sonuçlarına göre ise; 47,96±15,71, 29,26±8,38 değer kadar düĢtüğü bulunmuĢtur (p<0.001). Yapılan çalıĢmada baraitrik cerrahinin kilo vermede baĢarılı olduğu, BKĠ‟ni düĢürdüğü ve beden memnuniyetini pozitif anlamda yükselttiği görülmüĢtür. Sonuç olarak hastalar cerrahi sonrasında psikolojik, fiziksel ve metabolik olarak kendilerini daha sağlıklı hissettikleri bulunmuĢtur.
Beslenme ve Diyetetik Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Sağlık Bilimleri Fakültesi, Beslenme ve Diyetetik Bölümü, 2016. Tez Danışmanı: Prof. Dr. Murat Baş.
Keywords: Beslenme ve Diyetetik; Diyet--Beslenme--Obezite; Obezite; Beriatrik cerrahi; Beck Depression ölçeği; Multidimensional Body Self / Self Relationship Questionnaire; Yeme Tutumu Testi; Obesity; Bariatric surgery; Beck Depression Scale; Multidimensional Body Self / Self Relationship Questionnaire; Eating Attitudes Test